On the decomposition of the Esteban and Ray index by income sources - Elena Bárcena-Martín; Jacques Silber (Econometrics, 2018)
This paper proposes a simple algorithm based on a matrix formulation to compute the Esteban and Ray (ER) polarization index. It then shows how the algorithm introduced leads to quite a simple decomposition of polarization by income sources. Such a breakdown was not available hitherto. The decomposition we propose will thus allow one to determine the sign, as well as the magnitude, of the impact of the various income sources on the ER polarization index. A simple empirical illustration based on EU data is provided.
Keywords: D31; D63; J31; 330; decomposition; Esteban and Ray polarization index; income sources; polarization